An Improved Model of Physical and Emotional Social Defeat: Different Effects on Social Behavior and Body Weight of Adolescent Mice by Interaction With Social Support - Li, Man; Xu, Hang; Wang, Weiwen (Frontiers in Psychiatry, 2018)
Social stress is a prevalent etiological environmental factor that affects health, especially in adolescents. Either experiencing or witnessing a traumatic event during adolescence can increase the risk of psychiatric disorders, such as PTSD. The present study attempted to establish an improved social stress model to better distinguish the effects of physical and emotional social stress on behavior and physiology of adolescent mice. In addition, we investigated how social support affected these stress-induced changes in social behavior. On PND 28, male littermates were exposed to either physical stress (PS) or emotional stress (ES), afterwards, half of them were paired housed and the others were singly housed. PS mice were directly confronted with a violent aggressor using the social defeat stress (SDS) paradigm for 15 min/trial (with the total of 10 trials randomly administered during a week), while ES mice were placed in a neighboring compartment to witness the PS procedure. Our results indicate that both stressors induced an effective stress response in adolescent mice, but PS and ES had differential influence in the context - relevant social anxiety/fear and social interaction with peers. Additionally, social support following stress exposure exerted beneficial effects on social anxiety/fear in ES, but not PS exposed mice, suggesting that the type of stressor may affect intervention efficacy of social support. These findings provide extensive evidence that physical and emotional stressors induce different effects. Moreover, ES, rather than PS exposed mice seemed to benefit from social support. In summary, the study suggests that the paradigm will be helpful in investigating the effects of psychological intervention for treatment of stress-related psychiatric disorders.